2013
DOI: 10.5194/bg-10-891-2013
|View full text |Cite
|
Sign up to set email alerts
|

DOC-dynamics in a small headwater catchment as driven by redox fluctuations and hydrological flow paths – are DOC exports mediated by iron reduction/oxidation cycles?

Abstract: Dissolved organic carbon (DOC) exports from many catchments in Europe and North-America are steadily increasing. Several studies have sought to explain this observation. As possible causes, a decrease in acid rain or sulfate deposition, concomitant reductions in ionic strength and increasing temperatures were identified. DOC often originates from riparian wetlands; but here, despite higher DOC concentrations, ionic strength in pore waters usually exceeds that in surface waters. In the catchment under study, DO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
128
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(150 citation statements)
references
References 69 publications
19
128
2
1
Order By: Relevance
“…Inamdar et al, 2004). Knorr (2013) observed that Fe and DOC were exported to streams during rainfall events only if the preceding period allowed a pool of Fe and DOC to be created (Regime I). Inversely, after a rainfall event, a rapid transfer of Fe to the stream would require the prevention of oxidation and retention at the site (Regime II).…”
Section: Intermittent Connectivity and Ecological Consequencesmentioning
confidence: 99%
“…Inamdar et al, 2004). Knorr (2013) observed that Fe and DOC were exported to streams during rainfall events only if the preceding period allowed a pool of Fe and DOC to be created (Regime I). Inversely, after a rainfall event, a rapid transfer of Fe to the stream would require the prevention of oxidation and retention at the site (Regime II).…”
Section: Intermittent Connectivity and Ecological Consequencesmentioning
confidence: 99%
“…In the case of carbon the significance of the riparian zone is well established when it comes to both dissolved organic carbon (DOC) and CO 2 (e.g. Fiebig et al, 1990;Hinton et al, 1998;Oquist et al, 2009;Lyon et al, 2011;Winterdahl et al, 2011;Grabs et al, 2012;Knorr, 2013;Leith, 2015;Ledesma et al, 2015). However, the special biogeochemical conditions of the riparian zone also have consequences for the transport of widely different substances such as nitrogen (Hill, 1996;Cirmo and McDonnell, 1997;Sabater et al, 2003), phosphorus (Mulholland, 1992), base cations (Ledesma et al, 2013), aluminium (Cory et al, 2007), mercury , persistent organic pollutants (Bergknut et al, 2011) and pesticides (Vidon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Tank et al, 2012). While the accumulation of organic matter in unforested mires makes them the major source of DOC in the boreal landscape (Rantakari et al, 2010;Ågren et al, 2007), forested areas, which generally have the greatest areal extent in the boreal biome, also contribute large DOC concentrations because of the presence of organic-rich riparian soils Knorr, 2013).…”
Section: Introductionmentioning
confidence: 99%